Misi Allah pada Masa Intertestamental - Elisua Hulu (Jurnal Teologi Berita Hidup, 2020)
The people of God of the Old Testament and the people of God in the New Testament were linked during what is called the intertestamental age. This period is referred to as a state of vacuum which is marked by the absence of a demonstrative role of the prophet. The 400 year period of development, destruction, success and decline of the ruling nations was prophesied by God. The Old Testament Book of Daniel shows clearly that world history is proceeding according to God's sovereignty. Mission is God's work. The important thing from God’s mission is talking about God as a sender, where He is the source, initiator, dynamist, implementer and fulfiller of His mission. The method of study related to God's mission in the Interstestamental era is the method of studying literature, which describes it descriptively. The intertestamental period is the time when other nations know the God of Israel through their existence among them. This is a different way from what happened in the days of Solomon's kingdom where there was a temple in Jerusalem which became an attraction for Gentiles. The political, social, and economic situation in intertestamental times was a preparation for the mission of the church in New Testament times.Umat Allah Perjanjian Lama dan Umat Allah Perjanjian Baru dihubungkan dalam masa suatu yang sebut masa intertestamental. Masa ini disebut sebagai keadaan adanya kevakuman yang ditandai oleh tidak nampaknya peranan nabi secara demonstratif. Masa waktu 400 tahun mengalami perkembangan, kehancuran, kesuksesan dan kemerosotan negara-negara yang menguasai sudah dinubuatkan oleh Tuhan. Kitab Daniel dalam Perjanjian Lama memperlihatkan dengan jelas bahwa sejarah dunia berjalan sesuai dengan kedaulatan Allah. Misi adalah karya Allah. Hal penting dari misi atau pengutusan Allah berbicara tentang Allah sebagai pengutus, dimana Ia adalah sumber, inisiator, dinamisator, pelaksana dan penggenap misi-Nya. Metode pengkajian terkait misi Allah pada masa Interstestamental adalah dengan metode kajian pustaka, yang menguraikan secara deskriptif. Masa intertestamental adalah masa di mana bangsa-bangsa lain mengenal Allah Israel melalui keberadaan mereka di tengah bangsa-bangsa lain. Ini adalah cara yang berbeda dari yang terjadi pada masa kerajaan Salomo di mana ada bait suci di Yerusalem yang menjadi daya tarik bagi bangsa-bangsa lain. Situasi politik, sosial, dan ekonomi pada masa intertestamental merupakan persiapan bagi misi gereja pada masa Perjanjian Baru.